An innovative framework for incorporating iPhone LiDAR point cloud in digitized documentation of road operations - Srikulnath Nilnoree; Tsukasa Mizutani (Results in Engineering)
The transformation of road infrastructures with digital solutions is vital in response to the growing population in urban areas. Ensuring timely repairs of potholes, cracks, and other damages is essential for enhancing the overall quality of transportation networks. The integration of advanced technologies, such as Light Detection and Ranging (LiDAR), into road maintenance represents an emerging solution in engineering applications and infrastructure management. However, the current practices of as-is documentation in local road maintenance have limitations due to time restrictions and practicalities. To address these gaps and unlock the immense potential of iPhone LiDAR technology, this article proposes an innovative workflow that integrates iPhone 13 Pro LiDAR technology with Augmented Reality (AR) marks and the Global Navigation Satellite System (GNSS) to enable digitized multi-scene road maintenance documentation and revolutionize current practices. To handle the dynamic scenarios encountered in road maintenance, the study introduces object-based fine registration techniques. These techniques provide a simple, effective, and adaptable approach to improve alignment in multi-scenes with limited overlap. Following the fine registration process, the captured data is digitized to construct 2D elevation heat maps, offering advanced and comprehensive information for managing road maintenance operations. Through a case study, the practicality and value of utilizing iPhone LiDAR technology in real-world scenarios are highlighted. The findings underscore how this technology can significantly enhance road maintenance operations and contribute to more efficient and effective management of road infrastructure. The adoption of digital solutions and the utilization of iPhone LiDAR technology enable enhanced road maintenance practices and contribute to the ongoing development of urban environments.